2021
DOI: 10.1021/acs.jafc.0c06634
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Sulfur Heterocyclic Compounds That Contribute to the Acidic Odor of Aged Garlic Extract

Abstract: The aroma of aged garlic extract (AGE) has been recently characterized as a complexity of seasoning-like, metallic, fatty, and acidic notes; most of the important aroma compounds were identified in a previous study. Besides the 25 previously identified aromas of AGE, several of the odor compounds that contribute to the acidic notes were isolated and identified using various analytical techniques, including gas chromatography coupled with an olfactometry monitoring system (GC–O), accurate and high-performance p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Literature data on key odorants in vegetables can be divided into early works on crucial sensory active compounds, especially in Allium vegetables; some works are on other vegetables, mainly Brassica, and there are works, especially in recent years, on compounds migrating in the cold pressing of rapeseed oils, especially after roasting seeds [69,[100][101][102].…”
Section: Sulfur Compounds As Key Odorants In Vegetablesmentioning
confidence: 99%
“…Literature data on key odorants in vegetables can be divided into early works on crucial sensory active compounds, especially in Allium vegetables; some works are on other vegetables, mainly Brassica, and there are works, especially in recent years, on compounds migrating in the cold pressing of rapeseed oils, especially after roasting seeds [69,[100][101][102].…”
Section: Sulfur Compounds As Key Odorants In Vegetablesmentioning
confidence: 99%
“…To the best of our knowledge, this is the first report demonstrating that volatile components contribute to health‐promoting effects of AGE against cell damage. Recently, we identified more than 25 odor active compounds in AGE and found that these were mostly absent in fresh garlic (Abe et al, 2020, 2021). GC–MS analysis in the present study again revealed the significant change in the volatile components that occurs during the aging process of fresh garlic.…”
Section: Discussionmentioning
confidence: 99%
“…Allyl methyl sulfide, diallyl sulfide, allyl methyl disulfide, diallyl disulfide, trans-2-methyl-2-butenal, trimethylpyrazine and 3-hydroxy-butanoic acid, and ethyl ester were purchased from Tokyo Chemical Industry Co., Ltd. (Tokyo, Japan). The compounds cis/trans-2,4-dimethyl-1,3dithiolane, trans-2,6-dimethyl-1,4-dithiane, 2-vinyl-4H-1,3-dithiin, S-methylmethanethiosulfinate, and 3-vinyl-4H-1,2-dithiin were synthesized as described previously (Abe et al, 2020(Abe et al, , 2021. Antibodies against extracellular signal-regulated kinase (ERK), phospho-ERK, c-Jun N-terminal kinase (JNK), phospho-JNK, p38, and phospho-p38 were purchased from Cell Signaling Technology (Beverly, MA, USA).…”
Section: Materials and Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 ), which causes the unpleasant taste and aroma of garlic, is broken down into volatile substances such as allyl methyl sulfide and allyl mercaptan when consumed [ 10 , 11 ]. Due to this pungent odor and aroma, many people do not want to consume this crucial vegetable with many health benefits and because of this, the consumption of garlic remains very limited [ 1 , 10 ].
Fig.
…”
Section: Introductionmentioning
confidence: 99%